Implementasi Pembelajaran Kolaboratif dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam Siswa Sekolah Dasar Muhammadiyah 2 Surabaya - Muchammad Raffi Firdiansyah, Raffi; Muhammad Arfan Muammar; Hayumuti (EduInovasi: Journal of Basic Educational Studies, 2025)
This research aims to analyze the implementation of collaborative learning methods in increasing students' understanding of Islamic Religious Education (PAI) at SD Muhammadiyah 2 Surabaya. Using a qualitative approach with a case study method, this research involved PAI teachers, students and school principals as informants to obtain data through interviews, direct observation and documentation. The research results show that collaborative learning has a positive impact on student understanding, active involvement, and development of Islamic character. This method allows students to learn actively through group discussions, increases self-confidence, and strengthens social skills. The average student score increased from 72 to 85 after implementing collaborative learning, while the level of active participation of students also jumped significantly. However, there are challenges in classroom management, such as ensuring all students contribute equally and limited time in group discussions. These findings support the importance of the teacher's role as a facilitator who is able to manage groups effectively. This research concludes that collaborative learning is an effective method in improving learning outcomes and building student character, especially in the context of Islamic religious education. As a recommendation, the development of better teacher training and classroom management strategies is needed to optimize collaborative learning outcomes in the future.